Emily Windsnap and the tides of time - Kessler, Liz (Kessler, Liz. Emily Windsnap series, 2020)
When Emily makes a wish on a magic stone, she gets a glimpse of what the future holds--and it's a disaster! She tries to make things right, but each trip through time takes Emily to a future where things turn out badly for either the humans of Brightport or the merpeople of Shiprock. Plastic pollutes the ocean, garbage overflows the landfills, and the two towns are no longer getting along. Emily realizes she can't save her hometown and the ocean alone, but with help from her best friends, Shona and Mandy, she'll have to find a way to get humans and merpeople to work together. Will Emily be able to create a better future for everyone, including herself? This new adventure gives readers a glimpse at what Emily and her friends could be like as grown-ups, with a fresh story that explores how uniting communities can make a future that's bright for everyone.--